Unveiling the Potential: is the private sector poised to revolutionize the solar irrigation market in Ethiopia? - Adamseged, Muluken Elias; Abegaz, Dagmawi Melaku; Minh, Thai Thi (Elsevier, 2025)
The significance of small-scale solar irrigation is well documented. However, the understanding of its adoption and scaling remains to be seen. Using solar-powered pump technology in Ethiopia as a case study, we aim to investigate the factors influencing technology adoption and the private sector's emergence to take over the market. We used a systemic perspective to analyze the multifaceted aspects influencing the enabling environment. This study shows that actors' engagement in promoting solar irrigation technologies has converged. In particular, the growing and continuous engagement of the private sector with other key stakeholders plays a significant role. These have improved users’ awareness of solar irrigation over the years. However, perceived risk, cost barriers, financial constraints, and pre-and post-sales services remain hindering factors. The findings show that policy initiatives and the private sector's growth can create enabling environments. However, challenges related to limited technology availability, financial constraints, and policy implementation hurdles can impede the process. Addressing these challenges can create an environment that enables the adoption and scaling of solar-powered pumps and private-sector investments in Ethiopia’s irrigation innovations.